Digitisation of library materials in Nigeria: issues and considerations for information professionals (2007)
This article describes the potential role of digitisation in the development of Africa. It describes the efforts at the digital conversion of local information and resources held in some university libraries and national institutions in Nigeria. Theses and dissertations are the most commonly digitised, while other are newspapers, past question papers, manuscript and special collections. The article also explores issues for successful conversion of library materials to digital format and skills development opportunites and challenges in Africa. It submits that willingness to share experiences gathered on digitisation programmes would broaden the knowledge base and contribute to the development of digitised African local content.